Inconsistent calculation methodology for the eucapnic voluntary hyperpnoea test affects the diagnosis of exercise-induced bronchoconstriction. Issue 1 (18th December 2018) - Koch, Sarah; Sinden, Sean Michael; Koehle, Michael Stephen
Abstract : Introduction: The eucapnic voluntary hyperpnoea (EVH) challenge is used to screen for exercise-induced bronchoconstriction. Several criteria have been proposed to determine the decrease in lung function (fall index, FI) following EVH. We compared three published FI calculation methods to determine if they affect the diagnostic classification. Methods: The three FIs were calculated for 126 EVH tests. Spirometry was performed in duplicate at baseline and repeated 3, 5, 10, 15 and 20 min following 6 min of EVH. The higher of the two forced expiratory volume in 1 s (FEV1 ) measures at all time-points post-hyperpnoea was selected for the calculation of the FIs. The FIA was determined as the single lowest of the five postchallenge values, and a test was considered positive if FEV1 decreased ≥10 %. In FIB, a test was considered positive if FEV1 decreased ≥10% at two consecutive post-challenge time-points. The FIC was calculated identically to FIA, but was normalised to the achieved minute ventilation during the EVH challenge. Results: Calculation method affected the raw FIs with FIB generating the smallest and FIC generating the highest values (p<0.001) and a within-subject range of 7%±10%. The number of positive tests differed between the calculation criteria: FIA : 62, FIB : 48 and FIC : 70, p<0.001. Nineteen participants (15%) tested positive in one or two FI methods only, indicating that the FI method used determined whether the test was positive or negative. Discussion: Inconsistency in methodology of calculating the FI leads to differences in the diagnostic rate of the EVH test, with potential implications in both treatment and research outcomes.